An approach for bending and transient dynamic analysis of integrated thermal protection system with temperature-dependent material properties. (1st January 2017) - Gu, Liangxian; Wang, Yifan; Shi, Shengbo; Dai, Cunxi
Abstract: A C 0 higher-order layerwise finite element model combined with homogenization techniques for bending and transient dynamic analysis of integrated thermal protection system (ITPS) panel is presented. The ITPS panel is homogenized as an equivalent sandwich plate, and a reduced temperature field for the entire panel is derived. An advanced analytical equivalent model based on energy approach and Castigliano's theorem for the mechanical properties of the trapezoidal corrugated core is presented, which considers the effects of temperature-dependent material properties. The proposed layerwise theory which is developed for a sandwich plate, assumes linear, quadratic and cubic polynomial distributions of displacements for middle layer and linear polynomial distributions of displacements for top and bottom layers. And the effect of transverse normal strains is taken into account in the layerwise theory. A four-noded isoparametric element with 16 degrees of freedom per node is employed to model the equivalent sandwich plate. The accuracy of the proposed method is verified by comparison with the results by three-dimensional (3D) finite element analysis. It has been shown that the proposed method requires significantly less computational effort and agrees well with the finite element results.